Control of buoyancy-induced temperature and flow fields with an embedded adiabatic thin plate in porous triangular cavities - Varol, Yasin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2009)
Natural convection has been performed in an insulated horizontally thin plate embedded in a triangular enclosure filled with fluid saturated porous medium, numerically. Bottom and inclined wall of triangular enclosure are isothermally heated and cooled, respectively. Vertical wall of enclosure is adiabatic. Steady, two-dimensional, laminar governing equations, which are written with Darcy model, were solved with finite-difference method. Calculations are conducted for different lengths and locations of thin plate, different aspect ratios, and Darcy-modified Rayleigh number. Prandtl number was chosen as 0.71. It is observed that the change on plate location in vertical and horizontal axes makes small effect on heat transfer; however flow field and temperature distribution strongly affected from these parameters. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Porous media; Adiabatic thin plate; Triangular cavity